Analisis mindful parenting, konflik pekerjaan keluarga, dan psikopatologi pada orang tua bekerja - Wahyuni, Liza; Ardianti, Riski Dian; Nurlis, Nurlis (Holistik Jurnal Kesehatan, 2025)
Background: The prevalence of parents as workers with job characteristics varies across countries. Family work conflict is associated with poor parental mental health triggered by psychopathology such as anxiety, depression and parenting stress which results in inattentive parenting. Purpose: To determine the relationship of family work conflict and psychopathology namely anxiety, depression, parenting stress with attentive parenting in working parents. Method: A cross-sectional study was conducted on 324 working parents with children and adolescents aged 1-19 years. Data were collected at the Muhammadiyah 6 Integrated Islamic Elementary School and the Qur'an Education Institute in Indonesia from mid to late July 2024 by filling out sociodemographic forms, measuring work-family conflict, anxiety, depression, parenting stress and caring parenting. Results: Parents with shift work schedules, working full-time and 40 or more hours per week, showed significantly higher levels of work-family conflict than those with fixed or flexible schedules, working part-time and less than 40 hours per week. Correlation analysis found that there was a relationship between work-family conflict and psychopathology, namely depression, anxiety, parenting stress and attentive parenting where anxiety was found to have the strongest relationship with attentive parenting. Higher levels of work-family conflict were associated with lower parenting through higher levels of anxiety/depression symptoms and parenting stress.  Conclusion: There is a relationship between work-family conflict and psychopathology, namely anxiety, depression, parenting stress with attentive parenting and negative patterns where every increase in work-family conflict, anxiety, depression, parenting stress will decrease attentive parenting for children. Suggestion: Workplaces should implement family-friendly policies such as flexible work arrangements that help parents reduce anxiety, prevent depression and parenting stress to be able to balance the responsibilities and demands of their work and family roles.   Keywords: Conflict; Family Work; Parenting; Psychopathology.   Pendahuluan: Prevalensi orang tua adalah pekerja dengan karakteristik pekerjaan yang bervariasi di seluruh Negara. Konflik pekerjaan keluarga dikaitkan dengan kesehatan mental orang tua buruk yang dipicu oleh psikopatologi seperti kecemasan, depresi dan stress pengasuhan yang berdampak pada pola asuh yang kurang perhatian. Tujuan: Untuk mengetahui hubungan konflik pekerjaan keluarga dan psikopatologi yaitu kecemasan, depresi, stress pengasuhan dengan pengasuhan penuh perhatian pada orang tua bekerja. Metode: Sebuah studi cross sectional dilakukan pada 324 orang tua bekerja memiliki anak dan remaja berusia 1 sampai 19 tahun. Data dikumpulkan pada SD IT Muhammadiyah 6 dan Lembaga Pendidikan Qur’an di Indonesia dari pertengahan hingga akhir Juli 2024 dengan mengisi formulir sosiodemografi, pengukuran konflik pekerjaan keluarga, kecemasan, depresi, stres pengasuhan dan pengasuhan penuh perhatian. Hasil: Orang tua dengan jadwal kerja shift, bekerja penuh waktu dan 40 jam atau lebih per minggu, menunjukkan tingkat konflik pekerjaan-keluarga yang jauh lebih tinggi daripada mereka yang memiliki jadwal tetap atau fleksibel, bekerja paruh waktu dan kurang dari 40 jam per minggu. Ditemukan hasil analisa korelasi ada hubungan antara konflik pekerjaan keluarga dan psikopatologi yaitu depresi, kecemasan, stress pengasuhan terhadap pengasuhan penuh perhatian dimana didapatkan kecemasan memiliki hubungan paling kuat dengan pengasuhan penuh perhatian. Tingkat konflik pekerjaan-keluarga yang lebih tinggi dikaitkan dengan pengasuhan yang lebih rendah melalui tingkat gejala kecemasan/depresi yang lebih tinggi dan stres pengasuhan.  Simpulan: Ada hubungan antara konflik pekerjaan keluarga dan psikopatologi yaitu kecemasan, depresi, stres pengasuhan dengan pengasuhan penuh perhatian dan berpola negatif dimana setiap konflik pekerjaan keluarga, kecemasan, depresi, stres pengasuhan orang tua meningkat maka akan menurunkan pengasuhan penuh perhatian pada anak. Saran: Tempat kerja harus menerapkan kebijakan ramah keluarga seperti pengaturan kerja yang fleksibel  yang membantu orang tua mengurangi kecemasan, mencegah depresi dan stres pengasuhan untuk dapat menyeimbangkan tanggung jawab dan tuntutan pekerjaan dan peran mereka dikeluarga.   Kata Kunci: Keluarga; Konflik; Pekerjaan; Pengasuhan; Psikopatologi.